MENIMBANG DEMOKRASI DELIBERATIF DALAM PROSES PEMBENTUKAN HUKUM YANG DEMOKRATIS DI INDONESIA - Fadjar Sukma; Saparuli (IBLAM Law Review)
Citizens as subjects as well as objects of law have an important role in the  process of forming laws that apply as a model that becomes patterns of  interaction in the life of the state and society as well as an order of behavior that  must be fulfilled. This is also in line with the latent spirit of the Indonesian nation,  namely "consensus" in making a decision or policy. But now democracy in  Indonesia is only defined as the election of the president and vice president and  representative institutions to sit in parliament. After that, public participation in  various aspects of life seemed to be abolished, especially in terms of the formation  of a regulation or law which actually directly affects people's lives, even though  our constitution mandates that the highest power is in the hands of the people. A study on liberalized democracy popularized by Jurgen Hambermas emphasizes  the active participation of the community as a pillar in direct supervision and  inspection as well as on the formation of laws outside the parliament in order to  direct the quality of Indonesian law towards a better direction.